2020
DOI: 10.1080/09540962.2020.1763605
|View full text |Cite
|
Sign up to set email alerts
|

From enthusiasm to disenchantment: an analysis of the termination of Portuguese municipal enterprises

Abstract: This paper explores determinants of continuity and change of municipal organizations designed for service delivery. Focusing on the political and financial costs of termination, it addresses the question of what determines the process of voluntary closing of Portuguese municipal enterprisesa type of mixed firm with municipal control but an independent budget that operates under private labor lawfrom 1998 until 2012. The results suggest that the survivability of this type of organization relates with financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In addition to the literature examining the drivers behind the use of corporatized public services, studies have begun to emerge that analyze the termination and dissolution of corporatized public services, as well as the return of corporatized services in‐house. At the local government level, Camões and Rodrigues (2021) find that Portuguese municipalities experiencing financial pressure are more likely to terminate municipal corporations. At the organizational level, Andrews (2022) finds that corporatized services are less likely to be dissolved if they are majority public‐owned, but more likely to be dissolved when they are subject to greater political control.…”
Section: Current State Of Empirical Researchmentioning
confidence: 99%
“…In addition to the literature examining the drivers behind the use of corporatized public services, studies have begun to emerge that analyze the termination and dissolution of corporatized public services, as well as the return of corporatized services in‐house. At the local government level, Camões and Rodrigues (2021) find that Portuguese municipalities experiencing financial pressure are more likely to terminate municipal corporations. At the organizational level, Andrews (2022) finds that corporatized services are less likely to be dissolved if they are majority public‐owned, but more likely to be dissolved when they are subject to greater political control.…”
Section: Current State Of Empirical Researchmentioning
confidence: 99%
“…Is a similar phenomenon observed with public corporations? Meanwhile, local state‐owned enterprises have yielded mixed results (Camoes & Rodrigues, 2021; Overman & van Thiel, 2016; Voorn et al, 2017), which may come to undermine the perceived value of such reforms. More compelling evidence about the actual performance of public corporations, and about this performance is viewed by governments, would improve our understanding of the decisions leading to their creation.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Their findings show that re-municipalisation occurs more frequently in local governments with private contractors and is not primarily driven by political interests, but by the preferences of bureaucrats. Reverse contracting has also been a popular research topic in recent years Camöes and Rodrigues (2020). found that economic and financial rather than political aspects are the key drivers of reverse contracting.…”
mentioning
confidence: 99%